A new strategy for ultralow biofouling membranes: Uniform and ultrathin hydrophilic coatings using liquid carbon dioxide - Susanti, Ratna F.; Han, Yang Soo; Kim, Jaehoon; Lee, Young Haeng; Carbonell, Ruben G. (ELSEVIER SCIENCE BV, 2013)
Highly stable, uniform and ultrathin hydrophilic polymer coatings on the surface as well as in the pores of a PVDF microfiltration (MF) membrane are obtained by coating a hydrophilic monomer in liquid carbon dioxide (l-CO2) followed by subsequent crosslinking reaction. Polyethylene glycol diacrylate (PEGDA, M-n similar to 258 g/mol) is used as the l-CO2 soluble hydrophilic monomer source and azobisisobutyronitrile (AIBN) was used as a radical initiator. The extremely low surface tension and the low viscosity of l-CO2 result in ultrathin and uniform PEG coatings on the hydrophobic polyvinylidene fluoride (PVDF) microfiltration membrane. The chemical composition, morphology, and the depth profiles of the PEG-coated membranes are characterized in detail using X-ray photoelectron spectroscopy, scanning electron microscopy, electron probe microanalysis and energy dispersive X-ray microanalysis. Long-term permeation flux test using a bovine serum albumin solution shows that the 1.0 wt% PEGDA-coated membrane using l-CO2 exhibits 1.34 times larger BSA solution flux than that of the uncoated PVDF membrane, and 1.3 times larger flux than that of a commercial hydrophilic membrane. Fouling resistance estimation shows that the 1 wt% PEGDA-coated membrane exhibits similar to 30% lower internal fouling resistance than the pristine membrane, and similar to 24% lower internal fouling resistance than the commercial hydrophilic membrane. Crown Copyright (C) 2013 Published by Elsevier BY. All rights reserved.
Keywords: POLY(VINYLIDENE FLUORIDE) MEMBRANES; POLYPROPYLENE MICROPOROUS MEMBRANES; CROSS-LINKING APPROACH; BOVINE SERUM-ALBUMIN; POLY(ETHYLENE GLYCOL); ULTRAFILTRATION MEMBRANES; SURFACE MODIFICATION; MICROFILTRATION MEMBRANES; GRAFT-POLYMERIZATION; ANTIFOULING PROPERTY